The Diagnostic Value of the Vacuum Phenomenon during Hip Arthroscopy. (28th July 2011) - Rath, Ehud; Gortzak, Yair; Schwarzkopf, Ran; Benkovich, Vadim; Cohen, Eugene; Atar, Dan
Abstract : The diagnostic value of the vacuum phenomenon between the femoral head and the acetabulum, and time frame of its occurrence after application of traction is an important clinical question. The resulting arthrogram may outline the shape, location, and extent of cartilage lesions prior to arthroscopy of the hip joint. The presence, duration, and diagnostic information of the vacuum phenomenon were evaluated in 24 hips that underwent arthroscopy. The operative diagnosis was compared to the results of imaging studies and to findings obtained during a traction trial prior to arthroscopy. Indications for arthroscopy included avascular necrosis, labral tears, loose bodies, osteoarthrosis, and intractable hip pain. In 22 hips the vacuum phenomenon developed within 30 seconds after application of traction. The most important data obtained from the vacuum phenomenon was the location and extent of femoral head articular cartilage detachment and the presence of nonossified loose bodies. The vacuum phenomenon did not reveal labral or acetabular cartilage pathology in any of these patients. The vacuum phenomenon obtained during the trial of traction can add valuable information prior to hip arthroscopy. Femoral head articular cartilage detachment was best documented by this method. The hip arthroscopist should utilize this diagnostic window routinely prior to hip arthroscopy.